The Urgency of Reforming Regulations for Money Laundering in the Digital Era - Mashuril Anwar (PT FORMOSA CENDEKIA GLOBAL, 2023)
This article aims to examine the politics of criminal law in dealing with cyber-based money laundering and the urgency of updating regulations to combat money laundering in the digital era. The type of research used in writing this article is normative with a statutory approach. The collection of legal materials in this study was also supported by literature studies and analyzed qualitatively and deductively. Based on the discussion, at the normative level, it is still partial and has not been specifically regulated. Currently, cyber laundering crimes are only accommodated by several separate legal regimes that have not been able to reach the perpetrators of cyber laundering crimes. Countermeasures against money laundering in the digital era, like cyber laundering, are still governed by conventional regulations. Therefore, it is urgent to update regulations on dealing with cyber laundering crimes that can accommodate the complexity of the problem.